2002
DOI: 10.1139/y02-070
|View full text |Cite
|
Sign up to set email alerts
|

Blood-brain barrier permeability after gamma whole-body irradiation: an in vivo microdialysis study

Abstract: The effects of total-body irradiation on the permeability of rat striatal blood-brain barrier (BBB) to [3H]alpha-aminoisobutyric acid (AIBA) and [14C]sucrose were investigated using the microdialysis technique. Seven days, 3 and 6 weeks, and 3, 5, and 8 months after gamma exposure at a dose of 4.5 Gy, no modification of the permeability to both [3H]AIBA and [14C]sucrose was observed. But, in the course of the initial syndrome, we observed a significant but transient increase in the BBB permeability to the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 34 publications
1
65
0
3
Order By: Relevance
“…Little such infiltration was seen in non-irradiated mice given bone marrow transplantation (Vallieres and Sawchenko, 2003), indicating that the irradiation might compromise the integrity of the blood-brain barrier (Diserbo et al, 2002) and hence raising the concern that it might change the immune response in the brain. Addressing this issue, Turrin et al compared the brain expression of innate immune markers between normal and chimeric mice following LPS administration.…”
Section: Discussionmentioning
confidence: 99%
“…Little such infiltration was seen in non-irradiated mice given bone marrow transplantation (Vallieres and Sawchenko, 2003), indicating that the irradiation might compromise the integrity of the blood-brain barrier (Diserbo et al, 2002) and hence raising the concern that it might change the immune response in the brain. Addressing this issue, Turrin et al compared the brain expression of innate immune markers between normal and chimeric mice following LPS administration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the occurrence of a transient increase of BBB permeability after radiation exposure, though the duration seemed to vary among the reports, and it was suggested to strongly depend on the size and the physicochemical properties of the probes used for the assay. 27 Nakata et al 28 studied the effect of single irradiation on the permeability of the BBB in rat brains and found that the destruction of the BBB was detected as early as 1 day after irradiation with 20 or 40 Gy, reached its maximum after 3 days, and gradually decreased during the following few weeks. The degree of this destruction could become much greater when the irradiation dose increased to 80 Gy and the BBB disruption remained during the whole course of the experiment.…”
Section: Figmentioning
confidence: 99%
“…Аналогичные исследования в единичных случаях уже проводятся на пациентах. Было показа-но увеличение проницаемости при ежедневном фракционировании в 3 Гр и по достижению суммар-ной дозы в 30 Гр, в области головного мозга, погра-ничных с полем облучения, причем степень увели-чения была прямо пропорциональна дозе ионизиру-ющего излучения [10]. Для уменьшения долгосроч-ной токсичности предпочтительнее фракциониро-вание с разовой ежедневной дозой 2 Гр [27].…”
Section: Discussionunclassified
“…За последнее десятилетие сведения о молеку-лярных изменениях церебрального эндотелия, реак-ции астроглии, длительности и сроках открытия ге-матоэнцефалического барьера при фракциониро-ванном облучении представляют собой разрознен-ную информацию [10][11][12][13][14][15]. По-прежнему спорным и открытым вопросом в современной нейроонколо-гии остается проблема состояния когнитивной сфе-ры и качества жизни пациентов после цикла химио-или радиотерапии на фоне увеличения продолжи-тельности жизни [16,17].…”
unclassified